Effect of P2O5 on the viscosity of yellow phosphorus slag in electric furnace at high temperatures. (1st February 2023) - Lu, Zhibin; Lu, Hao; Huang, Lei; Kong, Lingxue; Li, Huaizhu; Bai, Jin; Guo, Zhenxing; Bai, Zongqing; Li, Wen
Highlights: As P2 O5 content increases, slag viscosity increases at high temperature, while it decreases at low temperature. The Si-O network structure of slag is polymerized by the increase of P2 O5 content. P-O-Si bonds are formed, which increase the polymerization degree of slag. nC2 S-C3 P solid solution is detrimental to crystallization of gehlenite. The increase of P2 O5 content reduces the average particle size of melilite crystals. Abstract: Phosphorus is an important raw material for chemical industry. The traditional production method is to heat phosphate rock, silica and coke in an electric furnace, and produce phosphorus by reduction reaction at high temperatures. Slag discharge is one of the key processes for the operation of electric furnace, so it is important to understand the flow behavior of phosphorus bearing slag. In this work, we investigated the effect of P2 O5 on slag structure and viscosity in SiO2 -CaO-Al2 O3 -MgO-P2 O5 system by experiments. Results shows that as the P2 O5 content increases, slag viscosity slightly increases at high temperatures, because the addition of P2 O5 increases the polymerization degree of the slag. However, when the temperature is below the liquidus temperature (Tliq ), the slag viscosity decreases. The increase of P2 O5 content led to a decrease in the n value of nC2 S-C3 P solid solution and the average particle size of solid phase, which is detrimental to the gehlenite formation. In order to avoid the effect of fluctuation in the P2 O5 content on slag discharge process in electric furnace, the discharge temperatures of slag should be higher than Tliq of the slag or the content of silicon and calcium should be 85 wt%.